GUIDELINES FOR DEVELOPING THE USE OF DIGITAL TECHNOLOGY IN PARCEL MANAGEMENT IN EDUCATIONAL INSTITUTIONS UNDER THE JURISDICTION OF THE PHRA NAKHON SI AYUTTHAYA SECONDARY EDUCATIONAL SERVICE AREA OFFICE - Ubonlawut , Nunthawadee; Dechsura , Chaiyot; Rupan , Phonthep (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims 1) to study the use of digital technology in parcel management in educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office 2) to present guidelines for developing the use of digital technology in parcel management in educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office, there are 2 steps: 1) study the use of digital technology in Supplies management in educational institutions Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office, the population includes educational institution administrators. Chief Procurement Officer Parcel officer Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office From 29 educational institutions, totaling 87 people, all data was collected everywhere. The research tool is a questionnaire. The questionnaire has the characteristics of a scale of 5 Level (Rating Scale) Statistics used in data analysis include averages and standard deviations. 2) Presentation of guidelines for developing the use of digital technology in supplies management in educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office By interviewing 7 experts by specific selection methods. The tools used in the research are interviews and Content data analysis. The research results found that; 1) Use of digital technology in parcel management in educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office, it was found that the overall condition was at a high level. The area with the highest average is the use of digital technology in parcel distribution, followed by the use of digital technology in parcel maintenance The use of digital technology to control parcels the use of digital technology in procuring supplies and the area with the lowest average is the use of digital technology in planning the demand for supplies, respectively. 2) Guidelines for developing the use of digital technology in supplies management in educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office, it was found that there should be action Breakdown by component of the five areas.